Prevalence of non-alcoholic fatty liver disease at obesity and its interrelation with cardio-vascular disease and 2nd type diabetes mellitus risk factors - G. A. Melnichenko; A. Yu. Yeliseyeva; M. V. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate prevalence of non-alcoholic fatty liver disease (NAFLD) in patients with obesity and to determine its interrelation with cardiometabolic risk factors of cardio-vascular diseases (CVD) and diabetes mellitus of the 2nd type (type 2 DM).Material and methods. Retrospective analysis of case records of 560 obese patients aged 18 to 55 years was carried out. At the investigation past history, anthropometric data, level of blood pressure were analyzed, blood lipid spectrum, activity of ALT, AST, markers of viral hepatites – HbsAg, HCV-at (to rule out viral etiology of liver disease), fasting and at 120-th minute of the standard glucose tolerance test blood glucose and immunoreactive insulin were determined. Insulin resistance was estimated by HOMA-IR score. Metabolic syndrome was verified by IDF (2005) criteria. Liver US was carried out to diagnose NAFLD.Results. During investigation NAFLD was revealed in 77,7% of patients. At multi-factor analysis of variance interrelation of NAFLD with CVD and type 2 DM risk factors, such as systemic hypertension, dyslipidemia, disorders of carbohydrate metabolism and insulin resistance was confirmed.Conclusions. Study results determine necessity of more careful investigation of patients with obesity and NAFLD for early diagnostics and treatment of cardiometabolic risk factors of cardio-vascular diseases and type 2 DM.